The Range Contraction and Future Conservation of Green Peafowl (Pavo muticus) in China - Mingxiao Yan (MDPI AG, 2021)
The Green Peafowl (Pavo muticus) is vulnerable to anthropogenic pressures and has undergone an extensive decline through much of its range in Southeast Asia. However, little is known about the changing distribution of Green Peafowl in China through historical periods. We described a 5000–6000 years distribution change of Green Peafowl in China by using historical archives. We examined the present distributions of Green Peafowl by using camera traps and transect surveys and predicted the suitable habitat to support future conservation planning for this species. Although Green Peafowl was once widely distributed across China, the species experienced a southward range retreat over the past 5000–6000 years and is now restricted to a small part of Yunnan. The results of prediction from maximum entropy modeling (MaxEnt) showed that the size of suitable habitat of Green Peafowl in Yunnan was 17,132 km2. The suitable habitat concentrated in nine prefectures of Yunnan and Pu’er, Chuxiong, and Yuxi accounted for 48.64%, 27.39% and 15.83%, respectively. These results suggest that central Yunnan can cover most of the current larger and more contiguous populations of Green Peafowl in China and should be protected. Moreover, some areas in southern Yunnan, such as Xishuangbanna, can be a candidate for reestablishing populations, given that the species disappeared in this region less than 20 years ago and has a large remaining habitat.